PENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN INTERAKTIF PADA SISWA KELAS III SDN 05 KABUPATEN MUKOMUKO - Harmaini, Harmaini (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
In the cycle of learning improvement studies conducted in class III SD Negeri 05 Mukomuko City by using interactive learning models on Indonesian subjects, teachers did not optimize learning so that some students were still found to be less active in learning. While in cycle I, these deficiencies were overcome by improving learning from prasiklus with the implementation of maximum interactive learning. In prasiklus, there are still students who have not been involved in learning, so in the first cycle, the teacher tries to get students involved by optimizing group discussions and group presentations. Based on the results of improved learning that has been carried out on Indonesian Language class III subjects at SD Negeri 05 Kota Mukomuko, it has been shown to show progress. This can be seen from the increase in student learning outcomes at each meeting. So that it can be concluded that it has succeeded in improving the learning outcomes of Indonesian students in grade III SD Negeri 05 Kota Mukomuko with a cooperative learning model